Corruption, democracy and control effectiveness of the state Коррупция, демократия и регуляторная эффективность государства - Filippova Irina G. (Problemi Ekonomiki, 2013)
The object of analysis is a state as a distributed system of decision making and the subject of analysis is its disfunction as a result of action of institutional factors, in particular, corruption as an informal negative institute. The obtained results provide grounds for doubts in positive influence of democracy upon socio-economic processes, including upon the level of perceptible corruption. This suggests that democracy facilitates dispersion of responsibility and alienation of science from control, since scientific knowledge is not a “mass product” and becomes less and less demanded from the ruling elite in Ukraine. The function of the science as an institutional factor of effectiveness of state control lies in development of concepts of non-discretional mechanisms of decision making and also formulation of clear criteria for assessment of results of activity of subjects endowed with authority of decision making, in order to increase the level of their responsibility. Thus, we speak about such institutional factors of state control effectiveness as social responsibility and social control. Объектом анализа является государство как распределенная система принятия решений, а предметом – ее дисфункция как результат действия институциональных факторов, в частности, коррупции как неформального негативного института. Полученные результаты дают основание усомниться также в положительном влиянии демократии на социально-экономические процессы, в том числе, и на уровень воспринимаемой коррупции. Это наводит на мысль о том, что демократия способствует распылению ответственности и отчуждению науки от управления, поскольку научное знание не является «продуктом массового спроса» и становится все менее востребованным со стороны правящей элиты в Украине. Функция науки как институционального фактора эффективности государственного управления заключается в развитии представлений о недискреционных механизмах принятия решений, а так же формулировке четких критериев для оценки результатов деятельности субъектов, наделенных полномочиями принятия решений, с целью повышения уровня их ответственности. Таким образом, речь идет о таких институциональных факторах государственной регуляторной эффективности, как социальная ответственность и социальный контроль.